Creativity and Innovation are Essential Skills for Increasing Alternative Income for Informal Sector Workers - Bakhri, Syaeful; Fanther, Refaldo; Kumala, Titi (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2024)
Skills influence a person's ability to find employment, and the ability to possess these skills significantly determines whether an informal sector worker can increase their income. The relevance of skill ownership to income growth is powerful, as skills and expertise greatly enhance a person's opportunities to find employment and start a business. This study examines which specific skills a person must possess to increase their income, particularly for informal sector workers. The research uses a qualitative approach with the Analytical Hierarchy Process (AHP) technique. It gathers information from 15 key persons, including prospective workers, informal sector workers, local government representatives, academics, and business community members. The results of this study identify several key skills, such as public speaking, adaptability, innovation, creativity, and problem-solving confidence. Based on the Hierarchical Process Analysis, two factors are the most dominant: Creativity, with a score of 23,94, and Adaptability, with a score of 23,73. According to this analysis, an informal sector worker can increase their income if they have creativity and adaptability.